A Kinetic Study of Manganese Leaching from Low-Grade Psilomelane Ore by Acetic-Tannic Acid Lixiviant - Zunita, Megawati; Rhamadhani, Risha Diah (ASEAN Journal of Chemical Engineering, 2021)
Kinetic leaching of psilomelane using tannic acid as reductant and acetic acid as an acidic modifier is investigated in terms of tannic acid and acetic acid concentration, solid-liquid ratio, particle size and temperature. Kinetic modelling using three models: shrinking core, shrinking particle, and diffusion-interface transfer model revealed that at room temperature leaching (30 °C), experimental data are best modelled using diffusion-interface transfer model, indicating the dissolution of Mn is more affected by reaction rate among reactants and their concentration in bulk volume rather than by transfer across the boundary layer. At higher temperatures (≥ 50 °C), the shrinking particle model fits the experimental data best, suggesting the prominence of the diffusion process boundary layer. The apparent activation energy obtained at two temperatures were 13.1 and 52.7 kJ/mol for lower and higher temperatures. Plot between rate constant and concentration yields reaction order to be 1.28 for tannic acid and 0.73 for acetic acid. A semi-empirical model for each temperature range is proposed to describe the overall manganese leaching efficiency.